Problems and Features of the Human Side of Digital Supply Chain Mechanisim - G. I. Andryushchenko; T. M. Gridneva; K. G. Tsaritova; M.V. Savina; A. V. Blinnikova (International Journal of Supply Chain Management, 2020)
Abstract—Digitization has become the dominant theme in discussions about the future of supply chains. Wherever there is a problem, there is the promise of a technological solution, using some combination of artificial intelligence or machine learning, big data, automation, and the Internet of Things. The article actualizes the problems of the impact of digitalization of supply chain on the formation and transformation of human capital and, above all, the formation of new competencies, knowledge and skills. The main components of human capital in the digital supply chain have been clarified and disclosed - knowledge and skills that bring income to its carriers and value added; features of formal and informal educational process; the necessity of measures to minimize the class of precariat, which does not have a modern level of development of human capital, are proved; The main directions of a qualitative improvement of human capital that are adequate to the challenges of the modern digital supply chain and globalization are identified. Digital supply chain management can transform a company’s ability to anticipate and serve customer needs, starting with a focus on world-class demand sensing; controlling product flows; and optimizing customer deliveries.